Penggunaan Konsentrat hijau untuk Meningkatkan Produksi Ternak Kelinci New Zealand White - Eko Marhaeniyanto; Sri Susanti (Faculty of Animal Science, Universitas Brawijaya, 2017)
The in-vivo experimental study on rabbit animals mixed of Moringa oleifera, Lamk(MOL), Gliricidia sepium, Paraserianthes falcataria and Ceiba pentandra leaf meal(1: 1: 1: 1 ratio) of 10%, 20% and 30% in concentrate feed (= green concentrate).The research was conducted at